I survived : The destruction of Pompeii, AD 79 - Tarshis, Lauren (Tarshis, Lauren. I survived, 2014)
"No one in the bustling city of Pompeii worries when the ground trembles beneath their feet. The beast under the mountain Vesuvius, high above the city, wakes up angry sometimes--and always goes back to sleep, but Marcus is afraid. He knows something is terribly wrong--and his father, who trusts science more than mythical beasts, agrees. when Vesuvius explodes into a cloud of fiery ash and rocks fall from the sky like rain, will they have time to escape--and survive the epic destruction of Pompeii?"--Back cover.